2016
DOI: 10.1007/s11307-016-0977-2
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo HER2-Targeted Magnetic Resonance Tumor Imaging Using Iron Oxide Nanoparticles Conjugated with Anti-HER2 Fragment Antibody

Abstract: The scFv-IONPs enabled HER2-specific tumor MR imaging, suggesting the potential of scFv-IONPs as a robust HER2-targeted MR contrast agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…hrUS = high-resolution ultrasonography, μCT = contrast-enhanced in-vivo computed tomography, MRI = 9.4T magnetic resonance imaging, PET = positron emission tomography, BOLD = blood oxygen level dependent, ASL = arterial spin labeling, DCE = dynamic contrast-enhanced, DWI = diffusion-weighted imaging. hrUS μCT 9.4T MRI spatial resolution very high (33 μm) very high (18 μm) high (100 μm) soft tissue contrast good poor very good metastases screening liver bone, lung all organ systems options for functional imaging Doppler 35 , contrast agents 16 , 17 , 36 , photoacoustic imaging 37 contrast agents 20 , combination with PET 38 alternative protocols (BOLD, ASL, DCE, DWI) 23 30 , contrast agents 17 , 39 , combination with PET 38 examination time very short (5 minutes) short (12.5 minutes) long (37.9 minutes) radiation exposure none yes (radiation dose depending on protocol and number of scans) none costs (purchase) moderate moderate high …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…hrUS = high-resolution ultrasonography, μCT = contrast-enhanced in-vivo computed tomography, MRI = 9.4T magnetic resonance imaging, PET = positron emission tomography, BOLD = blood oxygen level dependent, ASL = arterial spin labeling, DCE = dynamic contrast-enhanced, DWI = diffusion-weighted imaging. hrUS μCT 9.4T MRI spatial resolution very high (33 μm) very high (18 μm) high (100 μm) soft tissue contrast good poor very good metastases screening liver bone, lung all organ systems options for functional imaging Doppler 35 , contrast agents 16 , 17 , 36 , photoacoustic imaging 37 contrast agents 20 , combination with PET 38 alternative protocols (BOLD, ASL, DCE, DWI) 23 30 , contrast agents 17 , 39 , combination with PET 38 examination time very short (5 minutes) short (12.5 minutes) long (37.9 minutes) radiation exposure none yes (radiation dose depending on protocol and number of scans) none costs (purchase) moderate moderate high …”
Section: Discussionmentioning
confidence: 99%
“…To enable the visualization of the primary tumor as well as the detection of pulmonary or skeletal metastases, the body area scanned included the whole thorax, abdomen and pelvis (oversize scan). Cross-sectional CT images were reconstructed from the acquired radiographs with the “NRecon” Reconstruction software (Bruker Corporation, Billerica, USA) using established protocols 39 . For tumor volume measurement, the “CT An” software (Bruker Corporation, Billerica, USA) was used according to the manufacturers instructions.…”
Section: Methodsmentioning
confidence: 99%
“…N87 (human gastric cancer cell) tumor-bearing mice were prepared as reported previously 28 . [ 123 I] 4 -trastuzumab (2.2–4.1 MBq/ 60–150 μg, 150 μL PBS) was intravenously injected into the N87 tumor-bearing mice (n = 3).…”
Section: Methodsmentioning
confidence: 99%
“…This mode of administration has also been commonly used in other in vivo studies of nanoscale contrast agents with similar NP-size ranges. [33][34][35][36][37] Serum biochemical indices ( Figure 4A) and the results of main blood-cell analysis ( Figure S2) showed that all parameters were within the normal range at each time point. The body weight of mice also played an important role in the biosafety investigation of materials.…”
Section: Biocompatibility and Biodistributionmentioning
confidence: 96%